A Numerical Approach for the Integration of Sonic Boom Requirements into the Matching Chart - Samuele Graziani; Leonardo Ialongo; Davide Ferretto (Aerospace)
The Matching Chart is a well-established tool in conceptual and preliminary aircraft design, providing a graphical representation of performance requirements based on wing loading (W/S) and thrust-to-weight ratio (T/W). It helps define a feasible design space while estimating key parameters such as thrust, maximum takeoff weight, and wing area. This paper presents a new numerical approach aimed at incorporating constraints related to sonic boom generated by supersonic aircraft in flight within the Matching Chart. The sonic boom constraint is derived from high-fidelity CFD simulations on similar case studies and atmospheric propagation models within a non-uniform atmosphere. The methodology is evaluated on an 80-passenger, Mach 1.5 aircraft, a configuration aligned with recent industry research. By integrating environmental and regulatory factors, this work enhances the Matching Chart’s applicability to enable more sustainable future supersonic aircraft design.